The spatial organization of the epidermal growth factor receptor on the surface of colorectal carcinoma cells - Fournier, C (2015)
The discovery of the existence of the cell membrane has led to a search for its organization on a molecular scale. The advent of artificial lipid bilayers and the development of electron microscopy in the 1930’s provided direct visual evidence for the existence of the cell membrane and drove forward models of membrane structure based its known composition of proteins, lipids and carbohydrates. The fluid mosaic model of membrane structure, based on thermo- dynamics and newly developed protein structural studies of the time, placed integral globular membrane proteins within a fluid phospholipid bilayer. This model allowed for the association of proteins into groups and the possible mobility of proteins within the lipid bilayer. At the the same time fluorescence microscopy demonstrated movement of proteins in the plane of the lipid bilayer. Since then experimental techniques have been developed that show protein complexes of varying sizes do exist and so this gives us the opportunity to ask how receptor proteins fit into the molecular organization of the cell membrane. This thesis presents an investigation into how the epidermal growth factor receptor (EGFR) organizes in the cell membrane of colorectal carcinoma cells. First a new cell line for studying the receptor by stably expressing the epidermal growth factor receptor conjugated to enhanced green fluorescent protein (EGFR-eGFP) in SW620 cells was developed. This is an interest- ing cell line because it originates from a colonic adenocarcinoma that during the process of metastasis has lost the ability to express the EGFR. It therefore provided an environment for the expression of the fluorescent form of the receptor more in keeping with its natural environment. The technique of total internal reflection fluorescence (TIRF) microscopy was used to visualize the fluorescently tagged receptor in the cell membrane. This technique uses the principles of total internal reflection to excite fluorescence in molecules located only 100 nm into the cell. Because sources of fluorescence from outside the illuminated area are minimized individual fluorescent molecules can be imaged. The spots in the images, produced by the fluorophores, were detected using a single molecule detection and tracking algorithm. The intensities of these detected spots were analysed and compared with that from a single molecule of enhanced green fluorescent protein (eGFP). This gave an estimate of the number of receptors contained within each receptor complex. Before ligand binding most of the receptors were found to be located in complexes containing up to eight molecules and most frequently they were found in complexes of two molecules. Larger complexes of receptors were found to have formed after activation of the receptor by its ligand.